Agonismo y post‑identidad en el activismo artístico de la Venezuela del socialismo del siglo xxi - Renato Bermúdez Dini (L'Ordinaire des Amériques)
This article aims to analyze certain practices of artistic activism in recent Venezuela, to characterize them in a different way in relation to the more militant activism of the last decades of the last century. The cases of Dale Letra, Las Piloneras, El Bus TV and Labo Ciudadano are specifically analyzed. Starting from the notion of agonism, developed by Chantal Mouffe, these practices of artistic activism are studied as social relations that try to activate more horizontal and less personalistic forms for politics through artistic experimentation. Finally, the political implications of the concept of community are explored from the reflections of Roberto Esposito, to argue that these practices of artistic activism seem to start from a post-identity notion that implement less militant and partisan ways of weaving social ties in times of a worrying polarization of Venezuelan politics.